On the issue of the servise Tatars-Mishars in the Trans-Urals - D.Sh. Muftakhutdinova (Известия высших учебных заведений. Поволжский регион: Гуманитарные науки)
Backgrounds. The relevance of the study is due to the fact that during the popula-tion census in Bashkiria there is a tendency to rewrite the Tatar population of the North-Western regions of the Republic of Bashkortostan as Bashkirs, appealing to documents of the 18th–19th centuries, where the population of these regions could be called Bashkirs, but not in an ethnic, but in a class sense. The study aims to generalize information about the activities of the Mishar Tatars in the Trans-Urals, their role in suppressing the Bashkir uprisings of the first half of the 18th century and the incorporation of Mishar servicemen into the administrative bodies of the Orenburg Border Commission. Materials and meth-ods. A problem-chronological approach was used, which made it possible to analyze vari-ous aspects of the social policy of the Russian Empire in the dynamics of socio-political changes that occurred in the late 17th – first half of the 18th century in the Volga-Ural re-gion, as well as a historical-genetic method, which made it possible to examine historical facts and reveal the causes and factors that influenced the social development of the Mishar Tatars in the Volga-Ural region. The theoretical and methodological basis of the study was the conceptual provisions of scientific research in the field of studying the ethno-confessional policy of the Russian state on the national outskirts of the empire. Results. Based on the studied legislative sources and literature, the process of incorporation of the Mishar Tatars into the Russian state service as a military service class is revealed, in par-ticular as Cossacks, akhuns in the Bashkir darugs, regimental mullahs in the Bashkir-Meshcheryak army, as well as in the administration of the Orenburg Border Commission as translators, interpreters, and confidants. Conclusions. The role of the service Tatars from among the Mishars is multifunctional. On the one hand, they performed military and police functions. On the other hand, interpreters, translators, and clerks from among the Mishar tatars played a huge positive role in the management and study of the East, thereby contributing to the painless integration of the Kazakh steppe into the all-Russian space.